9514 1404 393
Answer:
(f×g)(2) = 3/4
Step-by-step explanation:
For each of the functions, put 2 where x is and evaluate the expression.
f(2) = (3 -2)/(2² +4) = 1/8
g(2) = 3×2 = 6
Then the product is ...
(f×g)(2) = f(2)×g(2) = (1/8)×6 = 6/8
(f×g)(2) = 3/4
Answer:
x = 1
y = -3
Step-by-step explanation:
if y = x - 4
then reorganise the first equation
4 (x - 4) = 9x -21
4x - 16 = 9x - 21
5 = 5x
x = 1
Answer:
There are 336 teenagers in the concert. Please Mark me brainliest if I am correct thank you and have a nice day.
Step-by-step explanation:
Answer:
y = -4x - 12
Step-by-step explanation:
y + 4 = -4(x + 2)
y = -4x -8 - 4
y = -4x - 12